27=-5x+120

Simple and best practice solution for 27=-5x+120 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=-5x+120 equation:



27=-5x+120
We move all terms to the left:
27-(-5x+120)=0
We get rid of parentheses
5x-120+27=0
We add all the numbers together, and all the variables
5x-93=0
We move all terms containing x to the left, all other terms to the right
5x=93
x=93/5
x=18+3/5

See similar equations:

| 4x^2+4×=0 | | x+x-72=478 | | 30x+12=6(5x+2 | | 6(5m-3)=72 | | 4.49x*x/4.49x+x=5700 | | 15+m=39 | | -(y2-2)=y2-5-y2 | | (2m-4)^2-4(2m-4)+3=0 | | 8^x=16 | | 5x+1-3x=7-(-2x-9) | | 10x-12=12-10x | | 4,3m-3.36=5.7m | | 216^x+1=16 | | 27-3m=8m-50 | | (3x-2)/4=4 | | 4x(2x+5)(x-6)=0 | | x+3(1+2x)=17 | | 5x-19=-4 | | -64=-4x-12 | | m+7=3+m+14 | | X-72x=478 | | 2/(x-3)+(1/4)=2 | | (2x-5)*2x-3/2=0 | | 1/2b+9/7=7/4 | | 7x9=(7x10)-(7x | | x/2-8=110 | | 3+10x=-67 | | 3(7-2x)=14(-1)-8(x-1) | | (2x+41)+127=180 | | 7x+32=9x-16 | | 3(x-2)+14=-25 | | (3x+9)=(4x-8) |

Equations solver categories